Do sex reversal procedures differentially affect agonistic behaviors and sex steroid levels depending on the sexual genotype in Nile tilapia?. Issue 4 (23rd August 2017) - Gennotte, Vincent; Akonkwa, Balagizi; Mélard, Charles; Denoël, Mathieu; Cornil, Charlotte A.; Rougeot, Carole
GRAPHICAL ABSTRACT: ‐ Males and females with XX, XY, or YY genotypes have particular behavioral and physiological traits. ‐ Sex chromosomes or hormonal sex reversal treatments may have an influence on brain sex differentiation and expression of agonistic behaviors. Abstract: In Nile tilapia Oreochromis niloticus, phenotypic males and females with different sexual genotypes (XX, XY, YY) have particular behavioral and physiological traits. Compared to natural XX females and XY males, XY and YY females and XX males expressed higher level of aggressiveness that could be related to higher levels of 17β‐estradiol and 11‐ketotestosterone, respectively. Our results suggest that the presence of a Y chromosome increases aggressiveness in females. However, since the same relationship between aggressiveness and the Y chromosome is not observed in males, we can hypothesize that the differences in aggressiveness are not directly dependent on the genotype but on the sex reversal procedures applied on young fry during their sexual differentiation to produce these breeders. These hormonal treatments could have permanently modified the development of the brain and consequently influenced the behavior of adults independently of their genotype. In both hypotheses (genotype or sex reversal influence), the causes of behavioral modifications have to be searched in an early modification of the brain sexual differentiation.